Building up eParticipatory decision-making from the local to the global scale. Study case at the European Higher Education Area. (June 2015) - Díaz Nafría, José María; Alfonso Cendón, Javier; Panizo Alonso, Luis
Highlights: Democratisation in globalised social systems must go beyond the nation–state model. This problem is addressed in both empirical and theoretical perspective. The empirical work correspond to an eParticipation experiment within the EHEA. Its technical, socio-technical and evaluation frameworks are careful reviewed. eSubsidiarity is proposed as enhanced eParticipation based on positive subsidiarity. Abstract: The social systems developed in the context of globalisation are further more complex that those arisen within the rule-of-law of the nation–states. The local, national and international relations impose into these social systems different force fields determining the space of possibilities in which they evolve. In this situation, the decision-making is correspondingly further more complex as to drive democratic participation from the root-level of individual members and stakeholders, all the way through until the global system. eParticipation represents a possibility to make it possible determined by the member perceptions of partaking in relevant decisions. A paradigmatic example of these globalised social structures is the European Higher Education System, in which very well defined local and national structures coexist with a normative field of globalised relations. Between 2010 and 2013 an eParticipation system was developed under EU support involving a significant number of universities from Europe and abroad. A flexible approach was used to adapt the system to the different contexts, whereas an analytical framework was set up to evaluate the experience in order to find guidance for future eParticipation developments. The socio-technical and analytical frameworks and the corresponding results are discussed aiming to propose a new architecture for eParticipation. This solution targets the challenges of the 21st century University in which the crossroads of learning analytics, eAdministration and eParticipation are deeply re-structuring the academic environment.